Preparasi Kolom Instalasi Pemurnian Biogas dalam Penentuan Kapasitas Serap Adsorben Arang Aktif dan Zeolit di Kecamatan Jabung - Wulandari, Ika Oktavia; Indahyanti, Ellya; Kamulyan, Budi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Biogas is one of the alternative renewable energy sources that are useful in our lives. Kecamatan Jabung located in Malang, has the potential to produce and develop this kind of energy resources. However, biogas contains many impurities such as H2O, CO2, and H2S that could have a negative impact. Therefore, it is necessary to purify the biogas by making an installation column. The purification process is carried out by utilizing solid adsorbents including zeolite and activated charcoal. However, because solid adsorbents have a certain capacity, an integrated indicator to determine the adsorbent capacity will be needed. The existence of this indicator will be helpful for the public to monitor whether the adsorbent needs to be regenerated or replaced. According to the trial result, we may conclude that silica gel is a promising indicator to determine H2O and H2S adsorption capacity. Meanwhile, lime water can also be used as an indicator of the adsorption capacity of CO2.